Critical revision of Physarales and Reticulariales (Myxomycetes) at the Natural History Museum London (BM) - Moreno, G.; Castillo, A.; Thüs, H. (Phytotaxa, 2024)
Light and scanning electron microscopy were applied to re-assess diagnostic characters of type specimens and critical specimens of Diachea radiata, D. splendens, D. subsessilis, Diderma arboreum, Didymium. laxifilum, D. leoninum var. effusum, D. trachysporum, D. trochus, Physarum bitectum, P. straminipes, Reticularia intermedia, R. jurana, R. liceoides, R. lobata and Wilczekia evelinae in the order Physarales and Reticulariales (Myxomycetes) from the collections at the Natural History Museum London (BM). The results were used to discuss published data and the type status for specimens studied.